WHAT TO TEACH: TOPICS AND SITUATIONS - Лемяскина, Н. В. ("МӘҢГІЛІК ЕЛДІҢ МӘҢГІЛІК ТІЛІ" Халықаралық симпозиум материалдары/ THE ETERNAL LANGUAGE OF THE ETERNAL NATION international symposium, 2016)
The process of teaching a foreign language is a complex one. It has to be broken down into components for purposes of study. They are presenting and explaining new material, providing practice and testing. It is the ‘presentation – practice – production’ paradigm. Шет тілін оқыту презентация-бекіту-нәтиже парадигмасына негізделуі мүмкін. Сөздік, сөйлеу, грамматикамен қоса топик, ситуация, түсінік сияқты аса «коммуникативті» категорияларды қолдану өте тиімді болады.
Keywords: what to teach; topics and situations; сөздік; сөйлеу; грамматикамен қоса топик; ситуация; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education